2003
DOI: 10.1021/op034117u
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of T2288:  From Bench Synthesis to Pilot Production

Abstract: A practical process to make N-(2,6-dimethylphenyl)-2-piperazin-1-yl-acetamide 1 is described, starting from piperazine 2 and N-chloroacetyl-2,6-xylidine 3. The unwanted N,N′-bis-alkylated product 4 can be removed by simple filtration of the reaction mixture, while the excess of piperazine remains in the aqueous phase after extracting the filtrate with toluene at 70°C. The product precipitates from the organic phase with 68% active yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…2-chloro-N-(2, 6-dimethylphenyl) acetamide (2) [13] was prepared by amixture of 2, 6dimethylbenzenamine (1, 0.1mol),Toluene, Water, NaHCO 3 (0.1mol) and Chloroacetyl Chloride(0.1mol) was added slowly at room temperature then maintained at refluex for 8-10hr.After completion of reaction ,cool the reaction mass to room temperature and filtered then wash with Toluene and Water, dried. A white color solid was obtained.Yield:98%.…”
Section: Results and Discussion: Synthesis Of 2-chloro-n-(2 6-dimethmentioning
confidence: 99%
“…2-chloro-N-(2, 6-dimethylphenyl) acetamide (2) [13] was prepared by amixture of 2, 6dimethylbenzenamine (1, 0.1mol),Toluene, Water, NaHCO 3 (0.1mol) and Chloroacetyl Chloride(0.1mol) was added slowly at room temperature then maintained at refluex for 8-10hr.After completion of reaction ,cool the reaction mass to room temperature and filtered then wash with Toluene and Water, dried. A white color solid was obtained.Yield:98%.…”
Section: Results and Discussion: Synthesis Of 2-chloro-n-(2 6-dimethmentioning
confidence: 99%
“…Foye et al reported a process to avoid the formation of bis alkylated product 11 ; however, this process has more steps and a much lower overall yield (2.1%). Guillaume et al reported a process to control the formation of bis alkylated product 11 with 68% yield. In this process the formation of compound 11 was controlled up to 7% and was removed by the simple filtration.…”
Section: Resultsmentioning
confidence: 99%
“…Among the bis alkylated product 11 and unreacted piperazine ( 5 ), we focused on the control of 5 , because the formation, control, and elimination of 11 were well studied and documented. , To reduce the piperazine content, compound 6 was converted into the hydrochloride salt and the phosphate salt followed by conversion into the free base. By converting into the hydrochloride salt, piperazine content was reduced to 0.02% from 0.5%, whereas converting into the phosphate salt, piperazine content was reduced to 0.008% from 0.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Despite its apparent simplicity, a convenient process to manufacture piperazine 12 was demanding to develop. We described this topic in a preceding paper.…”
Section: Resultsmentioning
confidence: 99%